(untitled) (Al-Academy, 2020)
The visual impression represents a compound process of a group of concepts that might be secondary and interrelated to constitute, in reality, a cognitive image stored in the memory that can be retrieved according the implications of the situation in which the individual lives in his environment, as it awakens in him an image from the sub consciousness, thus it gets stimulated, and it is among the tangible things. Since we live in our contemporary world under the development of knowledge, micro and wide technology of the devices, tools, materials, mechanisms, current developments and openness… etc. this transformation created visual impressions that the individual in general and the consumer in specific enjoys concerning his preferences for the image of the industrial product. Thus, the current research problem can be established through an attempt to discover the consumer’s awareness level and education, which depends on his visual impressions in preferring the industrial products that are characterized by high quality and technology in the operation mechanisms and the demonstration techniques, which generates functional and other aesthetic dimensions. Therefore, the researcher determined the following question: What are the functional and aesthetic dimensions of the industrial product and their implications on the creation of a visual impression on the consumer?The current research aimed at:1- Identifying the aesthetic and functional dimensions of the industrial product.2- Reaching the influences of the aesthetic and functional dimensions of the industrial product over the creation of the consumer’s visual impression. The research community is made of the industrial products designed in (2019) by Samsung, and a random sample represented by (automatic washing machine- electronic refrigerator- television screen) has been chosen. Therefore, these samples have been subjected to the analysis and investigation process to verify the aim of the current research. The following are some conclusions:1- The idea of the industrial designer, when implementing the product, requires achieving the functional dimensions of it represented by the ease of use according to clear operation mechanisms for the consumer through relying on advanced high efficiency systems. 2- The industrial product can have a high technology which reduces the consumer’s time and effort in the process of the functional use of this product in a way suitable with the concept of performance and achieves the benefit.